Appositive in Persian and Arabic - احسان اسمعیلی طاهری (مطالعات زبانی و بلاغی)
By comparing nominal-appositive group  in Persian  and noun-appositive clauses in Arabic concerning definition, structure, usage, divisions ,arrange of parts, grammatical function ,being definite and indefinite, we see parallelisms and parallelisms.